Artificial intelligence in Internet of things. Issue 4 (14th November 2018) - Ghosh, Ashish; Chakraborty, Debasrita; Law, Anwesha
Abstract : Functioning of the Internet is persistently transforming from the Internet of computers (IoC) to the 'Internet of things (IoT)'. Furthermore, massively interconnected systems, also known as cyber‐physical systems (CPSs), are emerging from the assimilation of many facets like infrastructure, embedded devices, smart objects, humans, and physical environments. What the authors are heading to is a huge 'Internet of Everything in a Smart Cyber Physical Earth'. IoT and CPS conjugated with 'data science' may emerge as the next 'smart revolution'. The concern that arises then is to handle the huge data generated with the much weaker existing computation power. The research in data science and artificial intelligence (AI) has been striving to give an answer to this problem. Thus, IoT with AI can become a huge breakthrough. This is not just about saving money, smart things, reducing human effort, or any trending hype. This is much more than that – easing human life. There are, however, some serious issues like the security concerns and ethical issues which will go on plaguing IoT. The big picture is not how fascinating IoT with AI seems, but how the common people perceive it – a boon, a burden, or a threat.